Forest management policies and oil wealth in Iran over the last century: A review. (30th June 2013) - Amiraslani, Farshad; Dragovich, Deirdre
Abstract: Deforestation is a problem in many developing countries. In Iran, the introduction of forestry management policies in the twentieth century coincided with a period of severe depletion in forest cover. This over‐utilization resulted from tree cutting for road construction, the establishment of sawmills and match factories, and in particular, the growing demand for charcoal and fuelwood for a rapidly increasing population. The formal forestry management policies initiated in the early 1900s were inadequately enforced, leading to continuing loss of forests through largely unregulated exploitation. Despite the discovery of oil in 1908 and natural gas in 1937, gas pipeline construction for domestic consumption was slow, kerosene was only gradually substituted for wood, charcoal consumption only fell steeply after 1960, and the established forest cover decreased sharply between 1970 and 1990. In 1991, the first of the post‐Revolution national Five Year Development Plans commenced and environmental protection was allocated significant budgetary support. The Five Year Plans implemented substantial reductions in livestock grazing in forests and encouraged reforestation, which partly offset the continuing forest removal. Using estimates based on fuelwood consumption in Brazil and USA, the forested area in Iran in 1850 would have disappeared by 2000 without the Government intervention which provided widespread access to fossil fuels. This energy‐source shift decreased local pressure on the dwindling forest resources and was reinforced by Government policies to conserve and extend forests.